Nicolas Sarkozy's Role in the 2008 Georgia Conflict: The "United West" Confronting Russia - D. Mikhaylov (Vestnik MGIMO-Universiteta)
This article examines the efforts of Nicolas Sarkozy, the President of the European Union (EU) at the time, in facilitating negotiations between Moscow and Tbilisi during the Georgia conflict in August-September 2008. While Sarkozy's primary objective was to end the bloodshed promptly, his strategic goals also encompassed preventing Georgia from falling back into Russia's sphere of influence and demonstrating the EU's capacity to independently resolve crises in the post-Soviet region.Sarkozy successfully persuaded Moscow and Tbilisi to accept his mediation, known as the "good offices," to normalize the situation in South Ossetia. Additionally, he garnered support from the United States and the EU, positioning himself as a representative of the entire "collective West" in dialogue with Russia. Confronted with the parties' entrenched positions, the French President occasionally resorted to altering the content of his proposed "six-point" peace plan without prior agreement, ultimately impacting the quality of the resulting agreements. These differing interpretations continue to hinder the reconciliation efforts between Moscow and Tbilisi.Through Sarkozy's mediation, a full-scale crisis in relations between Russia and the West was averted in August 2008. Significantly, Sarkozy was the first to officially articulate the threat of suspending all interaction between the "collective West" and Moscow if Russia employed military means to oppose EU and NATO expansion in the post-Soviet space. This article sheds light on Sarkozy's role in resolving the Georgia conflict while highlighting his strong stance against Russia's actions and aspirations in the region.